Pharmacological Activities of Some Medicinal Plants of Nepal - Ranjitkar, Rajeshwor; Maharjan, Sanam (Journal of Plant Resources, 2024)
Nepal has the most unique and valuable medicinal plants, owing to its diverse climatic conditions. Plant extracts as traditional medicine provide primary health coverage for about 65-80% of the world’s population, especially in the developing world. However, very limited biological research has been done in Nepal to date. This research aims to evaluate the pharmacological activity of eight medicinal plants from Nepal namely Anaphalis triplinervis (Sims) C.B.Clarke, Chlorophytum arundinaceuum Baker, Curculigo orchioides Gaertn., Girardinia diversifolia (Link) Friis, Rhododendron anthopogon D. Don, Swertia racemosa (Griseb.) Wall. Ex C.B.Clarke and two lichen species Dolichousnea longissima (Ach.) Articus and Hypotrachyna cirrhata (Fr.) Divakar, A. Crespo, Sipman, Elix & Lumbschsp. The ethanolic extracts of these plants were prepared by cold extraction process after which acute oral toxicity, antidiarrhoeal and antiulcer activity were analysed. All laboratory works were done in Natural Products Research Laboratory, Thapathali, Kathmandu, Nepal. The acute oral toxicity study showed no morbidity, mortality, toxicity signs, or symptoms at 2000 mg kg 1 in all medicinal plants except H. cirrhata. In the anti-ulcer test, C. orchioides, D. longissima, G. diversifolia, H. cirrhata and R. anthopogon significantly reduced gastric lesions in the ethanol-induced ulcer model at 500 mg kg -1 when compared to the standard drug, sucralfate (100 mg kg -1). The antidiarrheal effect was evaluated by gastrointestinal motility test at 500 mg kg -1 body weight in mice where the extracts of H. cirrhata and S. racemosa showed considerable antidiarrheal effect by reducing GI motility significantly compared to their respective control and standard drug loperamide (2 mg kg -1).